Modulation of Electronic States of Hybrid Lead Halide Perovskite Embedded in Organic Matrix. Issue 4 (12th November 2019) - Singh, Shivam; Dey, Amrita; Kolay, Santa; Kabra, Dinesh
Abstract : The modulation of electronic states of MAPbX3 perovskite nanocrystals (PNCs) (MA = CH3 NH3 + and X = Br − and I − ) is presented as a function of crystallite size in organic semiconductor matrix forming a type‐I heterostructure with bulk perovskites. Organic semiconductor molecule (4, 4′‐bis[9‐dicarbazolyl]‐2, 2′‐biphenyl [CBP] and bathocuproine [BCP]) precursors are mixed in different volumetric ratios with MAPbX3 perovskite precursors to prepare thin films. This results into an easy growth of MAPbX3 PNCs of tunable sizes from ≈110 to ≈10 nm in organic semiconductor matrix. A blue shift is observed in the photoluminescence peak (PLmax ) energy over a range of ≈200 meV for MAPbI3 PNCs embedded in the BCP matrix. However, PLmax energy tunes over ≈32 meV only with a similar volumetric concentration in the case of MAPbBr3 PNCs in the same BCP matrix. Moreover, the PL blue shift is even lower in the case of CBP matrix in comparison with BCP matrix for both the perovskites. This discrepancy could be resolved by determining the resultant crystallite size using X‐ray diffraction studies and the Debye–Scherrer formula. Results about blue shift in the PL peak can be explained using the classic particle‐in‐a‐box versus excitonic Bohr radius model under a weak confinement regime. Abstract : The modulation of electronic states of hybrid halide perovskites via crystallite size reduction is demonstrated. Perovskite nanocrystals (PNC) size is tuned by wt% doping in organic matrices via solution process. Weak confinement due to average size of crystallites that approaches toward the Bohr radius of the optically induced correlated electron‐hole pair results into significant blue shifted PL peak energy.